ENDOWMENTS IN EUROPEAN LAW state and perspectives - Veselinov, Jelena (Glasnik Advokatske komore Vojvodine, 2021)
Summary: Modern endowments have followed different paths in the national legislations of European countries, depending on the legal area to which those legislations belong. Nevertheless, in European countries with civil law systems, the basic characteristics of legal entities established in the spirit of endowment are the same or differ slightly. The idea of the European Union as a market with the free flow of people and capital inevitably resulted in the introduction of a complex set of rules that apply to the EU member states. Market relations, as well as an increasing number of endowments with various goals broader than ever have led to problems to which national legislations do not have solutions, or the solutions they offer are often contrary to EU principles. Therefore, it is necessary to regulate and resolve issues related to functioning of endowments and foundations in Europe by creating special rules at the EU level, by unifying or harmonizing rules that apply to these non-profit organizations. Seeing that his topic is of great importance for the process of development of EU private law in the non-profit sector, the present paper aims to provide a comparative analysis of both the existing legal regulations governing endowments and foundations in different national legislations of the EU member states and the proposals for creating uniform legal rules regarding this topic.
Keywords: Keywords: endowments, European Union, European Foundation